Does Controversial Science Call For Public Participation? The Case Of Gmo Skepticism - Christiansen, Andreas; Jonch-Clausen, Karin; Kappel, Klemens (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2017)
Many instances of new and emerging science and technology are controversial. Although a number of people, including scientific experts, welcome these developments, a considerable skepticism exists among members of the public. The use of genetically modified organisms (GMOs) is a case in point. In science policy and in science communication, it is widely assumed that such controversial science and technology require public participation in the policy-making process. We examine this view, which we call the Public Participation Paradigm, using the case of GMOs as an example. We suggest that a prominent reason behind the call for public participation is the belief that such participation is required for democratic legitimacy. We then show that the most prominent accounts of democratic legitimacy do not, in fact, entail that public participation is required in cases of controversial science in general, or in the case of GMOs in particular.